Household Solid Waste Management Practice of Women in Woldia Town, Amhara National Regional State, Ethiopia - Admasu, Shishigu Abi; Bazezew, Arega (Ethiopian Journal of Social Sciences, 2021)
Solid waste management (SWM) has become a major challenge in urban areas throughout the world. Unless people have an active involvement in SWM, it will result in environmental problems and health hazards. Hence, this study intended to assess women’s practice in effective household SWM at household level in Woldia town, Ethiopia. Mixed methods research with explanatory research design was employed for the study. Questionnaires were administered to 210 women who were selected through systematic sampling technique from three urban kebeles of the town. Interview, observation and FGD were used to collect qualitative data. Descriptive statistics and inferential statistics were used to analyze the quantitative data while thematic analysis was employed to interpret the qualitative data. The binary logistic regression model was used to identify factors that determined women’s participation in effective SWM at household level. The results showed that more than half (61%) of the respondents did not participate in effective household SWM, and yet, the majority (60%) of them still did not use alternative solid waste handling methods. The study also noted that lack of support from family members, inadequate support from the town municipality as well as cultural myths and beliefs were the challenges women faced to participate effectively in SWM. The study found that age, marital status, educational level and family size of respondents were the major determinants to participate in effective household SWM. From these results, it can be concluded that the young age group and the unmarried and/or divorced group of women were negligent in effective household SWM. Women’s awareness of SWM was found inadequate, and they were merely involved in managing solid wastes traditionally. The study recommended that supporting women in utilizing alternative and/or sustainable solid waste handling methods should be encouraged by the local government.